Non-invasive physical plasma for preventing radiation dermatitis in breast cancer: study protocol for a phase 3 randomised double-blind placebo-controlled trial (NIPP-RD III) - Dejonckheere, Cas S.; Layer, Julian Philipp; Sarria, Gustavo Renato; Wiegreffe, Shari; Glasmacher, Andrea Renate; Nour, Younèss; Scafa, Davide; Müdder, Thomas; Anzböck, Teresa; Giordano, Frank Anton; Stope, Matthias Bernhard; Schmeel, Leonard Christopher; et al. (Trials, 2025)
Radiation dermatitis (RD) is the most common side effect of breast irradiation, yet only few potent preventative and therapeutic options are available. Following encouraging results from a phase 1 and 2 trial on the topical use of non-invasive physical plasma (NIPP), a very well-tolerated physical treatment option to promote tissue regeneration generated from ambient air, we now present the study protocol for a planned phase 3 trial.
Gesehen am 23.07.2025